The role of pharmacogenomics in the tuberculosis treatment regime - Heinner Guio; Kelly S. Levano; Cesar Sánchez; David Tarazona (Revista Peruana de Medicina Experimental y Salud Pública, 2015)
Tuberculosis is a health problem worldwide with one-third of the population infected with the Mycobacterium tuberculosis bacilli. The first-line of treatment for tuberculosis includes the drugs Isoniazid (INH) and Rifampicin (RIF) metabolized in the liver. Drug metabolism is directly related to the genetic variation of NAT2 and CYP2E1 (associated with INH metabolism) and AADAC (associated with RIF metabolism), and the effects produced in an individual may be a fast, intermediate or slow metobolizer. Polymorphisms in genes of people in standard tuberculosis treatment can cause effects on drug metabolism with consequences of hepatotoxicity and even drug resistance. Countries have began clinical trials focusedon personalization of tuberculosis treatment to reduce the consequences for patients in treatment. In countries like Peru, where high rates of tuberculosis are recorded and therefore more people in treatment, the pharmacogenomic of individuals becomes a crucial tool for an optimum tuberculosis treatment. This review highlights the importance of having pharmacogenomic studies and having the identification of polymorphisms associated to the metabolism of the anti-tuberculosis drugs in our Peruvian population.